“Thus, I Give Up the Spear!”: Sovereignty and Violence against Animals: Review of Dinesh Joseph Wadiwel, The War Against Animals - McCorry, Seán (Humanimalia, 2016)
Dinesh Joseph Wadiwel. The War Against Animals. With a Foreword by Matthew Calarco. Leiden: Brill, 2015. xii+302 pp. 75.00.